2003
DOI: 10.1097/01.brs.0000048650.39042.58
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Relation Between Osteoporosis and Spondylosis in Postmenopausal Women As Evaluated by Bone Mineral Density and Semiquantitative Scoring of Spinal Degeneration

Abstract: Significant negative correlations were found between all bone mineral density data and the number of vertebral fractures (-0.524 < or r= r < or = -0.347; P < 0.05). Marginal/moderate positive correlations were observed between the osteophyte score and the bone mineral density data (0.263 < or = r < or = 0.580, P < 0.05), and between the disc score and the bone mineral density data (0.233 < or = r < or = 0.570, P < 0.05).CONCLUSIONS On the basis of the finding that spondylotic changes in postmenopausal women ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 28 publications
4
44
0
3
Order By: Relevance
“…Osteophyte formation was evaluated using the Nathan classification (0-4) and the total score (osteophyte score, 0-20) for L1/2-L5/S1 in this classification was also determined [15]. The degree of disc height narrowing was scored based on the scale of Miyakoshi et al [16], in which 0, 1 and 2 reflect a 0-20, 20-50 and [50% reduction in disc height compared with the L1-L2 disc, and the total score from the L2-L3 to the L5-S1 discs was defined as the disc score. A disc score of 0 corresponds to no disc degeneration.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…Osteophyte formation was evaluated using the Nathan classification (0-4) and the total score (osteophyte score, 0-20) for L1/2-L5/S1 in this classification was also determined [15]. The degree of disc height narrowing was scored based on the scale of Miyakoshi et al [16], in which 0, 1 and 2 reflect a 0-20, 20-50 and [50% reduction in disc height compared with the L1-L2 disc, and the total score from the L2-L3 to the L5-S1 discs was defined as the disc score. A disc score of 0 corresponds to no disc degeneration.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…Osteophyte formation was evaluated using the Nathan classification (0-4) and the total score (osteophyte score, 0-20) for L1/2-L5/S1 in this classification was also determined [18]. The degree of disc height narrowing was scored based on the scale of Miyakoshi et al [19], in which 0, 1 and 2 reflect a 0-20, 20-50 and [50 % reduction in disc height, respectively, compared with the L1-L2 disc. The total score from the L2-L3 to L5-S1 discs was defined as the disc score.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…Osteoporosis and osteoarthritis are both common conditions with a high prevalence in the elderly. Although an inverse relationship between osteoporosis and osteoarthritis has been suggested, these two degenerative conditions may certainly coexist [7,21]. Women in whom osteoporosis and osteoarthritis coexisted were significantly older than those having osteoarthritis or vertebral deformity independently [33], suggesting one of the reasons for a lack of association between BMD and LBP among women aged over 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have reported that in women with vertebral osteophytes or intervertebral disc degeneration, the BMD values were found to be significantly higher than in unaffected subjects, although almost all the measurement sites of BMD that proved this relation were either in the lumbar spine or the femur [3, 21,29], the exception being reports by von der Recke et al and Nanjo et al, where 599 measurements were taken at the distal radius [22,35]. It is suggested that higher bone mass may increase bone stiffness, and thereby increase loading of articular cartilage, leading to cartilage damage [30].…”
Section: Discussionmentioning
confidence: 99%